Перспективы развития технологий мобильной связи в Украине - Желтиков, А. В. (ХНУРЕ, 2019)
Prospects for the development of mobile communication technologies in Ukraine. Now Ukrainian mobile operators are doing a massive upgrade of equipment аfter issuing licenses for 3G and 4G. waiting for licenses for LTE 900 and 5G
Keywords: развитие технологий; мобильная связь; LTE 900; 5G